A narrative review on wastewater-based epidemiology as a strategy for disease surveillance in the Philippines - De Luna, Melissa Ellaine V. (Animo Repository, 2023)
Wastewater management in the Philippines has been a severe problem as the country lacks centralized sewage systems. As a result of improper wastewater management, the environment is prone to contamination, and communities are at risk of exposure to infectious diseases. This paper discussed the potential of Wastewater-Based Epidemiology (WBE) as a strategy for disease surveillance in the Philippines. Specifically, the paper provide the definition and its application to bacteria, parasites, and viruses, identify the challenges and limitations of WBE, determine and assess various evidence related to WBE in the Philippines, and discuss the future of WBE in the Philippines. The study performed a narrative review to synthesize existing literature on Wastewater-Based Epidemiology (WBE) in the Philippines, exploring its applications, challenges, and future directions in disease surveillance. Relevant articles related to WBE were obtained from reputable databases such as Google Scholar, Scopus, and Web of Science. Nine articles were included and assessed in the study. These studies reported the presence of pathogens in wastewater, sewage-polluted rivers, and irrigation waters in the Philippines. Several countries worldwide have shown that WBE is a valuable tool in detecting disease prevalence at a community level. In the Philippines, limited studies demonstrated that WBE can be a feasible approach to detect infectious agents in wastewater from various sources. The studies highlighted limitations in detecting low pathogen concentrations, wastewater treatment inefficiencies, and the persistence of antibiotic-resistant bacteria in irrigation sources, raising concerns about data reliability and public health implications. Critical gaps included small sample sizes, limited geographic coverage mainly in Metro Manila, and methodological variations, necessitating broader studies encompassing diverse regions and standardized methodologies for robust disease surveillance across the Philippines. Overall, WBE can be a complementary approach to clinical surveillance for detecting and monitoring diseases in the country. However, for a successful implementation of WBE in the country, adopting a holistic and integrated approach is crucial. It is recommended to conduct further studies applying WBE in targeting other pathogens and to create maps of hotspot areas. Establishing collaboration with government and private organizations is also recommended to conduct WBE studies in the Philippines at a larger scale.